Upaya Meningkatkan Hasil Belajar Peserta Didik dalam Pembelajaran IPAS Melalui Pendekatan Inquiry di Kelas VI SD Negeri Naikoten 2 Kupang : Upaya Meningkatkan Hasil Belajar Peserta Didik dalam Pembelajaran IPAS Melalui Pendekatan Inquiry di Kelas VI SD Negeri Naikoten 2 Kupang - Antonius Suban Hali; Kurniayu T. R. A. Ratu, Lusia F. Sabu Koten (STKIP Subang, 2025)
This study aims to improve students' learning outcomes in science learning on fossil energy material through the inquiry approach in class VI of Naikoten 2 Kupang Elementary School. The method used is Classroom Action Research (CAR), conducted in two cycles, each consisting of the stages of planning, implementation, observation, and reflection. Data collection techniques were carried out through observation of teacher and student activities, as well as learning outcome tests. The research subjects were 25 Grade VI students, consisting of 13 boys and 12 girls. The results showed a significant improvement in learning outcomes. Mastery learning increased from 44% in the pre-cycle to 68% in the first cycle, and reached 84% in the second cycle. Thus, it can be concluded that the application of the inquiry approach can improve students' learning outcomes in science learning on fossil energy material.